Study guides

☆☆

Q: What does 3 plus 6x equals 4x plus 9?

Write your answer...

Submit

Related questions

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

4x-3+6x+3 4x+6x=10x -3+3=0 10x is the answer!

6X + 3 = 2X + 19Subtract 3 from each side:6X = 2X +16Subtract 2X:4X = 16Divide by 4X = 4

If: 6x-6 = 4x Then: x = 3

6x + 3 = 2x + 5 4x = 2 x=1/2

It is an equation and the value of x is 4

2x+9=6x-3 Therefore 4x=12 -->x=3

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3

2x + 4x + 3 = 6x + 3

x = -3

Multiply the first by 3 and the second by -2

4x plus 3 plus 2x is equivalent to expression 6x plus 3.

6x + 14 = 20 + 4x ------ Combine like terms (subtract 4x and 14 from both sides). 2x = 6 --------------------- Divide by 2. x = 3

4x+6x=30 is the same as: 10x=30 so we divide by 10 and get: x=3 (I do not see how this relates to calculus, but O.K.)

4x-6=6x. subtract 4x so -6=2x. divide by 2 so -3=x

4x+9=2x-6 2x=-15 x=-7.5 x equals -7.5.

It is: x = -3 and y = -6 or as (-3, -6)

If x = 3, (4 x 3) + 14 = 26 and (6 x 3) + 8 = 26.

8x2 + 6x - 9 = (2x + 3)*(4x - 3)

4 + 2x

If you mean: 4x+3 = 6x-9 then the value of x works out as 6

2x-4=6x+8-8= -82x-12= 6x-2x= -2x-12= 4x/4=/4-3=x

8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)

3

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1